Pathogenesis, treatment, and prevention of arterial hypertension in Type 2 diabetes mellitus patients - V. S. Volkov; E. V. E.V. Rudenko; S. A. Rokkina (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To study arteriolar blood flow velocity and salt consumption in patients with Type 2 diabetes mellitus (DM-2) and arterial hypertension (AH); to clarify the causes and pathogenetic mechanisms of the latter.Material and methods. In total, 258 patients with DM-2 and AH were examined (mean age 54+1,16 years, disease duration 9,8+0,91 years). The control group (CG) included 110 age-matched healthy people. Taste sensitivity to salt (TSS), 24-hour urinary sodium excretion, and microcirculatory Doppler ultrasound were performed.Results. In patients with DM-2 and AH, decreased TSS resulted in involuntary increase of salt intake with food, which was confirmed by increased urinary sodium excretion. Arteriolar blood flow was significantly decreased in DM-2 participants, which indirectly pointed to arteriolar vasodilatation in AH.Conclusion. Volume-dependent mechanism (hypervolemia) plays a leading role in AH genesis among DM-2 patients. This should be taken into consideration while planning treatment and prevention strategies in individuals with DM-2 and AH.